Otimização e sustentabilidade de agroecossistemas - Rodrigues, Dielle Oliveira Filocre (2018)
Many researches have sought to evaluate the level of sustainability in agroecosystems through tools of sustainable indicators systems. However, many references have not been found in the literature on mathematical modeling in agroecosystems with proposals that involve the three pillars of sustainability. In this sense, this research aims to build an optimization model that determines the largest possible production of agroecosystems, keeping them within a stable level of sustainability, given a sustainability index. For the construction of the optimization model, the secondary data obtained from the study carried out by Reis (2013) were used as a basis for the sustainability indicators selected by the link to the characteristics of the environment and the IDS sustainability assessment tool (S3 ) for the definition of the decision variables, the technological data and the constraints of the problem formulated. To solve the problem, we used the geometric programming, whose implementation was done in MATLAB with the help of the CVX toolbox. The results found present an optimal solution for both the model and the sustainability index (IS), considering that even if production is maximized, there are stable levels of sustainability for agroecosystems. It should be highlighted that this research is a differential in relation to the optimization models found in the literature regarding the tripod of sustainability, and, mainly, the implementation of the geometric programming to solve the problem and validation of the optimization and sustainability model in agroecosystems.